Revealing Short-Term Precursors of the Strong M > 7 Earthquakes in Southern California From the Simulated Stress–Strain State Patterns Exploiting Geomechanical Model and Seismic Catalog Data - Bondur, Valery G.; Gokhberg, Mikhail B.; Garagash, Igor A.; Alekseev, Dmitry A. (Frontiers in Earth Science, 2020)
Since 2009, the stress-strain state of the earth’s crust in Southern California region is being monitored through geomechanical modelling taking into account the ongoing seismicity with magnitudes M >1. Every new earthquake is assumed to cause a new defect in the Earth's crust, leading to redistribution in the stress-strain state. With half-monthly stress-strain state updates, we found that both strong earthquakes with M ~ 7 that occurred in the area in 2010 and 2019, had been preceded by the anomalies in the strength parameter 𝐷 (indicating how close the rock is to its ultimate strength), which had emerged a few weeks to months before the main shock at a distance of 10–30 km from the future epicenter. Over the course of monitoring (nearly the decade), this approach has neither produced false alarms, nor missed events with M>7 falling within the modeling area.